2021
DOI: 10.48550/arxiv.2111.05879
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Insights on Entanglement Entropy in $1+1$ Dimensional Causal Sets

Abstract: Entanglement entropy in causal sets offers a fundamentally covariant characterisation of quantum field degrees of freedom. A known result in this context is that the degrees of freedom consist of a number of contributions that have continuumlike analogues, in addition to a number of contributions that do not. The latter exhibit features below the discreteness scale and are excluded from the entanglement entropy using a "truncation scheme". This truncation is necessary to recover the standard spatial area law o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…(1.48). The equivalence between the von Neumann entropy 10 A derivation of the same can also be found in [36,37].…”
Section: Spacetime Entanglement Entropy Of Quantum Fieldsmentioning
confidence: 86%
See 2 more Smart Citations
“…(1.48). The equivalence between the von Neumann entropy 10 A derivation of the same can also be found in [36,37].…”
Section: Spacetime Entanglement Entropy Of Quantum Fieldsmentioning
confidence: 86%
“…These violations are "small" and become negligible when suitably averaged over the ensemble. Adding to this is the work of [27] where the SJ eigenfunctions in the d = 2 causal diamond were examined in more detailed. They found that the eigenfunctions beyond the knee were highly fluctuating at and "below" the discreteness scale.…”
Section: Ssee In the Causal Setmentioning
confidence: 99%
See 1 more Smart Citation